6‐Gingerol suppresses tumor cell metastasis by increasing YAPser127 phosphorylation in renal cell carcinoma. Issue 1 (14th September 2020) - Xu, Shan; Zhang, Haibao; Liu, Tianjie; Wang, Zixi; Yang, Wenjie; Hou, Tao; Wang, Xinyang; He, Dalin; Zheng, Pengsheng
Abstract: According to the World Health Organization, the incidence and mortality rates of renal cell carcinoma (RCC) are rapidly increasing worldwide. Serious side effects caused by immune therapy and resistance to targeted drug therapy are urgent clinical problems facing kidney treatment. There is increasing global interest in developing natural products with a reduced number of side effects as adjunctive therapeutic options for RCC. Ginger is a spice and herbal remedy used worldwide, and 6‐gingerol is a major pharmacologically active ingredient in ginger. In our study, we found that 6‐gingerol suppressed RCC cell migration and metastasis in vitro and in vivo. Moreover, reduction in MMP2, Slug, and Vimentin protein levels was observed following 6‐gingerol treatment of 786‐O and ACHN cells. Furthermore, we revealed the mechanisms underlying the ability of 6‐gingerol to inhibit RCC cell migration and metastasis. 6‐Gingerol increased yes‐associated protein (YAP) ser127 phosphorylation and reduced YAP levels in cell nuclei. We also used a series of loss‐of‐function and gain‐of‐function experiments to support our results. Western blot results showed that MMP2, Slug, and Vimentin protein expression was downregulated in YAP‐silenced cells and upregulated in YAP‐overexpressing cells. Transwell data demonstrated that YAP suppressed RCC migration ability. Immunofluorescence images showed that 6‐gingerol decreased YAP levels, leading to disordered F‐actin and a reduction in cell lamellipodia. Overall, our results indicated that 6‐gingerol is a potential antimetastatic compound for use in kidney therapy.